Composition and Performance Evaluation of SBS/SBR Modified Emulsified Asphalt for Tack Coat on Airport Pavement. (11th November 2022) - Wang, Kaiwei; Xie, Xiangbing; Li, Guanghui; Shao, Jinggan; Bao, Meng; Wang, Mingwei; Zhu, Xianglei; He, Yahui
Abstract : Asphalt concrete pavement is gradually being adopted in cement concrete pavement repair and paving due to its short construction period and low vibration to aircraft. However, the performance of the interlayer binder is the critical factor affecting the paving effect. For the preparation of interlayer high-performance emulsified asphalt suitable for airport pavement, the type and dosage of modifier and emulsifier were taken as factors and levels for the orthogonal test. Combined with the evaporation residue, softening point, penetration, ductility, and Engla viscosity indexes, the range analysis was carried out to determine the optimal dosage of modifier and emulsifier. Furthermore, the dynamic shear rheology test (DSR), fluorescence microscope test, TG-DSC test, and shear and tensile tests were used to evaluate the technical properties of SBS/SBR modified emulsified asphalt. These results showed that the best blending mass ratio of SBS/SBR modified emulsified asphalt is 1.5% SBS + 3% SBR + 1% emulsifier. Temperature sweep at 48°C, compared with SBS/SBR modified emulsified asphalt, the complex shear modulus ( G ∗ ) of SBS/SBR modified emulsified asphalt increased by 71% and 75%, while the rutting factor( G ∗ /sin δ ) increased by 83% and 86%, respectively, which indicates that its shear deformation resistance and rutting resistance have been significantly improved. The Han curve indicates that the SBS/SBR modifier has excellent compatibility with asphalt and can maintain a stable state at a lower frequency. Before demulsification, SBS/SBR modifier and emulsified asphalt formed a stable spatial network structure. After demulsification, the continuous phase and the dispersed phase were more closely integrated, so that the emulsified asphalt exhibited better bonding performance. At different temperatures, by increasing the spraying volume, the shear and tensile strength of SBS/SBR modified emulsified asphalt increased first and then decreased. At 25°C, the maximum shear and tensile strengths are 0.86 MPa and 0.65 MPa. This study demonstrated that SBS/SBR modified emulsified asphalt formed a stable spatial network structure, giving it excellent technical properties, and can be widely used for tack coat on airport pavement.